2020
DOI: 10.1016/j.psj.2019.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Feeding high-oleic peanuts to meat-type broiler chickens enhances the fatty acid profile of the meat produced

Abstract: Early feeding trials using peanut meal prepared from normal-oleic peanuts helped to identify peanuts as a suitable alternative feed ingredient for poultry. Yet no studies to date have examined the use of high-oleic peanuts ( HO-PN ) as a feed ingredient for meat type chickens. Therefore, this study aimed to determine the effect of feeding whole unblanched HO-PN on the fatty acid profile of the meat produced from broilers. At hatch male chicks were randomly placed in raised wire cages, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 39 publications
4
27
1
Order By: Relevance
“…White varieties are similarly dominated by oleic and linoleic acids but at slightly higher proportions ( Afify et al, 2012 ). Broiler chickens fed diets high in oleic acid were found to have a higher FCR, as well as reduced muscle and carcass weights ( Toomer et al, 2003 ). Similar long chain fatty acids have also been shown to inhibit enzyme activity which could result in muted responses of exogenous feed enzymes ( Kido et al, 1984 ).…”
Section: Discussionmentioning
confidence: 99%
“…White varieties are similarly dominated by oleic and linoleic acids but at slightly higher proportions ( Afify et al, 2012 ). Broiler chickens fed diets high in oleic acid were found to have a higher FCR, as well as reduced muscle and carcass weights ( Toomer et al, 2003 ). Similar long chain fatty acids have also been shown to inhibit enzyme activity which could result in muted responses of exogenous feed enzymes ( Kido et al, 1984 ).…”
Section: Discussionmentioning
confidence: 99%
“…Crespo and Esteve-Garcia ( 2001) reported that feeding broilers a diet with increased amounts of polyunsaturated fatty acids reduced the rate of abdominal fat deposition in broilers. Toomer et al (2020) found that broilers fed high oleic peanuts exhibited lighter carcasses and yielded smaller portions of breast meat, than broilers fed a more conventional corn-soy diet. As sales of chicken meat have shifted from a whole carcass basis to individual parts and pieces, it is critical producers and processors continuously monitor changes in part/portion yield (Toomer et al, 2020).…”
Section: Broiler Carcass Yieldmentioning
confidence: 94%
“…Moreover, replacement of lard with perilla seed oil, which is similar to linseed oil in fatty acid composition, within the diet of yellow-feathered had no impact on animal growth, or feed intake (Cui et al, 2019). Toomer et al, (2020) found feeding broilers high oleic peanuts had no impact on feed efficiency, or final body weight. Based on the above, the potential exists to modified dietary fatty acid composition without negatively impacting broiler efficiency and growth.…”
Section: Broiler Performancementioning
confidence: 97%
See 2 more Smart Citations